The results of surgical treatment of arteriovenous fistula thrombosis of local intravenous catheter thrombolysis - Umut M. Muratbekova; Viacheslav N. Kravchuk; Andrey N. Shishkevich; Shamil M. Asadulaev; Valerii S. Ermakov; Artem S. Fedorov; Evgeniy I. Umantsev; Vadim V. Dalinin; Daria P. Vereshchak (Clinical Medicine (Russian Journal), 2026)
The aim of the study is to assess the short and medium-term outcomes of surgical treatment for arteriovenous fistula (AVF) thrombosis, using the novel method of local intravenous thrombolysis that we have developed. Material and methods. The study analyzed the clinical data from 158 patients who experienced arteriovenous fistula thrombosis between 2021 and 2024. Two groups of patients were formed: 1) the study group consisted of 77 patients who underwent the first stage of the “local intravenous catheter thrombolysis” method developed by us, the second stage was balloon angioplasty of an arteriovenous fistula; 2) the control group consisted of 81 patients who underwent open thrombectomy from an arteriovenous fistula. In this study, hemodynamic parameters of arteriovenous fistulas were analyzed in the preoperative and postoperative periods. Additionally, the following parameters were evaluated: duration of surgical intervention, cumulative patency of the AVF, duration of permanent vascular access at 1 and 3 months post-surgery, and duration of patient hospitalization. The study also involved a comparative analysis of costs of surgical procedures and hospital expenses between the two groups studied. Results . During the 30-day follow-up period, a statistically significant difference in cumulative patency rates of arteriovenous fistulas was observed between the two groups (p = 0.044). This indicates a more favorable postoperative outcome in the study group. By day 90 of follow-up, the difference between the groups had levelled off (p= 0.632). Conclusions. Therefore, the use of our developed method is recommended to improve short-term arteriovenous fistula patency outcomes, while further research with a longer follow-up is required to evaluate long-term effectiveness.